Pengaruh Literasi Fiqih dalam Kitab Fathul Qarib Terhadap Kualitas Ibadah Shalat Fardhu Santri - Awaludin, Rizky; Jumari, Jumari (ILJ: Islamic Learning Journal, 2025)
The focus of this study is to examine the extent to which santri's understanding of the contents of the Fathul Qarib book influences the quality of the implementation of fardhu prayers at the Miftahul Mubtadiin An Nur Islamic Boarding School, Krempyang, Nganjuk Regency. The Fathul Qarib book, as one of the basic fiqh references in the Shafi'i school of thought, plays an important role in shaping the religious understanding of santri, especially in terms of worship. Through a quantitative approach with a correlational research type, this study examines the relationship between the level of santri's understanding of the contents of the book and the quality of their worship practices in their daily lives. The research population included santri who actively participated in activities at the Islamic boarding school, with simple random sampling techniques applied to select respondents in order to obtain a representative sample. Data collection techniques involved distributing closed questionnaires, documenting worship activities, and directly observing the performance of fardhu prayers. The results of the analysis using simple linear regression indicated that the level of understanding of the Fathul Qarib book showed a significant positive correlation with the quality of fardhu prayers performed by the students.